Association between alcohol consumption and symptom severity and quality of life in patients with fibromyalgia - Kim, Chul H (BioMed Central, 2013)
INTRODUCTION: Although alcohol consumption is a common lifestyle behavior with previous studies reporting positive effects of alcohol on chronic pain and rheumatoid arthritis, no studies to this date have examined alcohol consumption in patients with fibromyalgia. We examined the association between alcohol consumption and symptom severity and quality of life (QOL) in patients with fibromyalgia. METHODS: Data on self-reported alcohol consumption from 946 patients were analyzed. Subjects were grouped by level of alcohol consumption (number of drinks/week): none, low (≤3), moderate (>3 to 7), and heavy (>7). Univariate analyses were used to find potential confounders, and analysis of covariance was used to adjust for these confounders. Tukey HSD pairwise comparisons were used to determine differences between alcohol groups. RESULTS: Five hundred and forty-six subjects (58%) did not consume alcohol. Low, moderate, and heavy levels of alcohol consumption were reported for 338 (36%), 31 (3%), and 31 patients (3%), respectively. Employment status (P <0.001), education level (P = 0.009), body mass index (P = 0.002) and opioid use (P = 0.002) differed significantly among groups with drinkers having higher education, a lower BMI, and a lower frequency of unemployment and opioid use than nondrinkers. After adjusting for these differences, the measures including the number of tender points (P = 0.01), FIQ total score (P = 0.01), physical function (P <0.001), work missed (P = 0.005), job ability (P = 0.03), and pain (P = 0.001) differed across groups, as did the SF-36 subscales of physical functioning (P <0.001), pain index (P = 0.002), general health perception (P = 0.02), social functioning (P = 0.02), and the physical component summary (P <0.001). Pairwise comparison among the 4 groups showed that the moderate and low alcohol drinkers had lower severity of fibromyalgia symptoms and better physical QOL than nondrinkers. CONCLUSIONS: Our study demonstrates that low and moderate alcohol consumption was associated with lower fibromyalgia symptoms and better QOL compared to no alcohol consumption. The reasons for these results are unclear. Since recent studies have demonstrated that γ-Aminobutyric Acid (GABA) levels are low in fibromyalgia, and alcohol is known to be a GABA-agonist, future studies should examine whether alcohol could have a salutary effect on pain and other symptoms in fibromyalgia.